SOSIALISASI PENATALAKSANAAN KEGAWATDARURATAN PSIKIATRI DI INSTALASI GAWAT DARURAT RUANG IGD RSJ CISARUA - Dina Hartini,; Grace Evelyn, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
People with mental disorders in the community have increased so that those who experience psychiatric emergencies have also increased. In line with this, it is necessary to treat psychiatric emergencies according to the proper method so as not to endanger patients, health workers, families and the community. The aim of this research is to identify the description of psychiatric emergency management in the Emergency Room of a Mental Hospital. The type of research used is descriptive. The population is 730 medical recorddata of patients who visit the ER of the RSJ. Collecting data with a retrospective approach using secondary data. Data analysis using percentages. The research results obtained were 576 respondents (78.9%) with behavioral observations and 154 respondents (21.1%) with fixation/restrain measures. The researcher's analysis of the main purpose of handling emergencies is to use drugs so that they can calm the patient and reduce aggressiveness, and medical personnel, both nurses and doctors, carry out the necessary examinations. The conclusion is that emergency psychiatric treatment is prioritized with psychopharmacological therapy, while restraint is carried out if the patient's condition cannot be calmed and endangers himself and others